2020
DOI: 10.1097/dss.0000000000002076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2-Octylcyanoacrylate Versus 5-0 Fast-Absorbing Gut During Linear Wound Closures and the Effect on Wound Cosmesis

Abstract: BACKGROUND Although the use of 2-octylcyanoacrylate (OCA) in cutaneous surgery offers increased efficiency, there is scant data comparing scar outcomes achieved with OCA versus 5-0 fast-absorbing gut suture (FG). OBJECTIVE To compare scar cosmesis achieved with OCA versus FG for surgical wound closure. MATERIALS AND METHODS A total of 44 patients with postoperative defects of at least 3 cm were included. Half of each wound was randomized to receive closure with either OCA or FG. At 3 months, patients and 2 bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Split-scar models have been used in the past to assess cuticular suturing techniques. [8][9][10][11][12][13][14][15][16][17] Enrolment and follow-up were conducted from June 6, 2018, to September 25, 2020, at the UC Davis Department of Dermatology. This study was approved by the University of California, Davis Institutional Review Board and the ClinicalTrials.gov Identifier: NCT05074199.…”
Section: Methodsmentioning
confidence: 99%
“…Split-scar models have been used in the past to assess cuticular suturing techniques. [8][9][10][11][12][13][14][15][16][17] Enrolment and follow-up were conducted from June 6, 2018, to September 25, 2020, at the UC Davis Department of Dermatology. This study was approved by the University of California, Davis Institutional Review Board and the ClinicalTrials.gov Identifier: NCT05074199.…”
Section: Methodsmentioning
confidence: 99%
“…18,19 Three studies which were included in the nal analysis compared the use of fast-gut sutures to cyanoacrylate adhesive, two studies compared FG to traditional PP sutures, and one compared different sized (5-0 and 6-0) FG sutures together. 8,9,[20][21][22][23] Risk of bias was considered low across all studies with regards to the randomization process, deviations from the intended result, outcome data, and selection of the desired result (Supplementary 1). Although overall risk was believed to be low, some concerns were present with measurement of outcome data as patients were unable to be blinded during the randomization process and were aware of their treatment group in 3 manuscripts.…”
Section: Literature Search and Risk Of Bias Assessmentmentioning
confidence: 99%
“…9,23 Two studies reported data related to patient opinion of nal cosmetic outcome and there was no difference between closures using FG vs. CA (Table 3). 22,23 Complications A total of 40 complications were reported across all wound closures (Table 4). The most common complication noted with FG sutures was infection (n=8, 3.3% of overall cases, Table 4).…”
Section: Comparison With Cyanoacrylate Tissue Adhesivementioning
confidence: 99%
See 1 more Smart Citation
“…The total score ranges from 6 to 60 with a lower score representing more normal appearing skin on the scale. The POSAS has been validated when 2 independent observers are used [18] and has been used in numerous surgical studies [12,13,17,[19][20][21][22][23][24][25]. The scar outcome was evaluated in person by the patient and 2 blinded observers who were not present during the intervention.…”
Section: Assessmentsmentioning
confidence: 99%